THE USE OF READING STRATEGIES IN ACADEMIC READING BY INDONESIAN LEARNERS - Erni (International Journal of Educational Best Practices, 2021)
This case study explores the Indonesian learners' reading strategies and identifies high and low-group learners' reading strategies. Semi-structured interviews, questionnaires, and open-ended questions were triangulated for validity and reliability data. Several findings were revealed. The Indonesian learners read critically and varied through cognitive, metacognitive, and affective strategies. They applied more cognitive strategies than metacognitive and affective strategies, which was less helpful and less encouraged to think critically. Technology advances, self concept, and time have affected the strategies used. High and low group learners also read differently in terms of cognitive, metacognitive, and affective strategies. The high group learners read efficiently, critically with various reading strategies, while the low group learners are more literal, attractive, but straightforward, and specific in reading strategy. This implied that students need to be facilitated with proper reading strategies and reading facilities and use metacognitive strategy to enable critical thinking and affective strategy to overcome anxiety, fear, and relaxation. The socio-cultural strategy needs to be used by learners to reach the four skills required by the Indonesian new curriculum. Meanings were shaped by social interaction and cultural context, which then created fun learning and a conducive learning environment.